PENGARUH PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE 5E BERBANTUAN LDPD TERHADAP PEMAHAMAN KONSEP DAN KETERAMPILAN PROSES SAINS PADA MATERI LARUTAN PENYANGGA - Diani Yola Lestari; Febrian Solikhin; Salastri Rohiat (University of Bengkulu, 2023)
[The Effect of Application of The LDPD-Assisted Learning Cycle 5E Learning Model on Understanding Concepts and Science Process Skills in Support Solution Materials] This study aims to determine the significant average difference in students' understanding of concepts and science process skills on buffer solution material. This type of research is a quasi experiment with a post-test only control group. This study used two classes, namely an experimental class with the application of the 5E learning cycle model and a control class with treatment as usual. This research was conducted at MAN 1 Bengkulu City. The research sample was class XI IPA 1 and XI IPA 4 which were randomly selected. Class XI IPA 1 as experimental class and XI IPA 4 as control class. The research instruments in this study are observation sheets, science process skills, and test questions. The data analysis technique used is the hypothesis test, namely the t-test for understanding concepts and the Mann-Whitney test for science process skills. Based on the results of the concept understanding hypothesis test, a significant 2-tailed value of 0.008 was obtained. The significance value is <0.05 so it is concluded that there is a significant average difference in concept understanding between the experimental class and the control class. Based on the results of the Mann-Whitney test, a significant value of 2-tailed 0.01 was obtained so that the significant value was <0.05. The test results showed that there was a significant average difference between the experimental class and the control class on process science skills.